Estrategias para el mejoramiento de la produccion de habichuelas: Control de mosaico comun, antracnosis, bacteriosis comun y anublo de halo - Davis, J. (International Center for Tropical Agriculture, 1987)
The backcrossing method is the most appropriate to incorporate resistance to BCMV, anthracnose, and halo blight without affecting snap bean quality. When improvement is less specific and includes characteristics such as plant adaptation, yield, and stand, it is possible to use the reccurrent screening method, which consists of conducting several crossing and screening cycles. Mutagenesis can be used to change a simple heritage characteristic such as seed color. Participants to the workshop on snap bean improvement in Latin America feel that CIAT's involvement in snap bean research would create interest among the directors of the agricultural research systems of several countries and would be the 1st step towards a greater and more integrated effort in the vegetable field. Besides, snap bean could be a pilot crop in research and training programs. (CIAT)